(untitled) (Global Journal of Computer Science and Technology, 2024)
Healthcare is evolving in surprising ways even for experienced professionals New technologies worldwide are being used in unexpected ways beyond just speeding up diagnostics and predicting care needs through biotechnology AI in healthcare is making transformative and disruptive advances Countries like the US Switzerland the UK and China are already home to some of the largest biotech and pharmaceutical companies and research programs In the UK AI is helping radiologists identify lung cancer with greater accuracy while Germany s genomic researchers are integrating AI to customize therapies based on the genetic profile of each tumor Researchers in Switzerland have already developed CRISPR-based therapy to cure sickle cell disease and another hemoglobin-affecting genetic disorder beta Thalassemia